1980
DOI: 10.1159/000265095
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Desquamation in the Adult-Mouse Cornea A Correlative TEM-SEM Study

Abstract: The central as well as peripheral corneal epithelium of normal young adult mice consisted of light (young), medium (mature) and dark (hypermature) cells based upon their brightness under the scanning beam. Multiple holes of either partial or full thickness were observed in these cells and were more common in medium and dark cells. Small as well as large mounds devoid of microvilli also were found in medium and dark cells. TEM of the corneal epithelium revealed the presence of small and large cytoplasmic vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

1982
1982
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 2 publications
2
8
0
2
Order By: Relevance
“…Previously, we have reported that purified Pseudomonas aeruginosa toxin A injected beneath the fused eyelid of 5-day-old mouse pups, resulted in toxemia and death of these animals within 24 h [1], Results from this study correlated well with previous work from this laboratory in which we used tox+ bacteria to infect pups [5] as well as with clinical cases of P. aeruginosa infection in human infants [2], Since only the unwounded, immature and not the young adult ocular surface epithelium is easily penetrated by P. aeruginosa, we initiated studies to carefully examine and compare the morphology of each type of surface epithelium [6,7], In this work, we found that there is virtually no morphologically detectable tear-1 Supported by United States Public Health Service Grants EY-02986 (LDH), EY-01935 (RSB) and AI-14671 (BHI) from the National Eye Institute and the National Institute of Allergy and Infectious Diseases. film in the pup, whereas it is present, although thin, in the young adult.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previously, we have reported that purified Pseudomonas aeruginosa toxin A injected beneath the fused eyelid of 5-day-old mouse pups, resulted in toxemia and death of these animals within 24 h [1], Results from this study correlated well with previous work from this laboratory in which we used tox+ bacteria to infect pups [5] as well as with clinical cases of P. aeruginosa infection in human infants [2], Since only the unwounded, immature and not the young adult ocular surface epithelium is easily penetrated by P. aeruginosa, we initiated studies to carefully examine and compare the morphology of each type of surface epithelium [6,7], In this work, we found that there is virtually no morphologically detectable tear-1 Supported by United States Public Health Service Grants EY-02986 (LDH), EY-01935 (RSB) and AI-14671 (BHI) from the National Eye Institute and the National Institute of Allergy and Infectious Diseases. film in the pup, whereas it is present, although thin, in the young adult.…”
Section: Introductionsupporting
confidence: 75%
“…film in the pup, whereas it is present, although thin, in the young adult. We also found that patterns of epithelial cell desquamation were different [6,7], In further work, we sequentially examined the histopathological events which occur following bacterial injection beneath the fused eyelid [8,9], From these studies, we have established that the first step in P. aeruginosa invasion of the intact ocular surface involves adherence of the bacteria to the peripheral corneal and conjunctival epithelium. This event is extremely rapid, and occurs within 5 min after bacterial injection.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on mouse cornea epithelium correlating scanning and transmission electron microscopy (Hazlett et al 1980) revealed that structures previously suggested to be full-thickness cell holes really represent different stages of local circumscipt cell impressions or full-thickness holes. Consequently, it was argued that scanning electron microscopy alone is not sufficient to identify these structures, because microvilli within the grooves appear similar whether they belong to the surface of the cell beneath, or they are projections from the posterior wall of an open cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of the barrier function is an important ance, indicating a loss of surface reticulation (Hazlett et al, 1980;Pfister, 1973;Fig. 2).…”
Section: Epitheliummentioning
confidence: 99%